Legislar? Um estudo do papel do legislativo municipal na produção de leis no interior do Paraná - Miranda, Aline Vons (2015)
With the 1988 Federal Constitution municipalities acquire financial, adminstrative and political autonomy counting with importants prerrogatives regarding public politicy production relevant to citizien. Considering that, the presente study discuss councilors action regarding one of theirs main activities, legislate. Therefore it was analise the presented bills in nine municipalities of Parana State on the period from 2009 to 2012. The aim is to analise the bills content brought by the municipal Legislative and discuss the relations of Executive and Legislative in the law-making process. Thereunto it was resort to some legislative activities indicators as such the data rate and success rate dominance. The theme, scope and effect are part of a classification of the bills. In reference to the bills theme, the Legislative is a potent producer of honorific, social and urban bills. On the other hand, the Executive produce economic and administrative bills, result of their constitutional prerogatives. Regarding the scope, the Legislative bills ar majority individual and sectoral. On the effects of proposals, council members generally prefer not to submit bills that burden the population directly, but in a diluted form.